Trapezio-metacarpal arthritis: functional and radiographic results at an average 5-year follow-up using trapeziectomy associated to a modified Ceruso’s suspensionplasty. - Concina, Chiara; Crucil, Marina; Saggin, Giorgio; Gherlinzoni, Franco (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: Trapezial-metacarpal arthritis (TMA) is a common and highly disabling pathology. Trapeziectomy and Ceruso’s suspensionplasty is described for moderate-severe stages. The aim of the present study was to assess functional and radiographic results at an average 5-year follow-up using a modified Ceruso’s technique where the Abductor Pollicis Longus (APL) is passed twice around the Flexor Carpi Radialis (FCR) and a suture mini-anchor in the base of the first metacarpal is used to further stabilize the thumb.Methods: 85 consecutive modified Ceruso’s suspensionplasty were performed from 2012 and 2018. All the patients were evaluated at an average 5.1-year follow-up (21-96 months). Subjective patient satisfaction rate, NRS, DASH score, abduction angle, Kapandji score and pinch strength using functional tests were assessed. The scapho-metacarpal distance was measured at follow-up radiographs.Results: 90.6% of the patients were satisfied by the treatment. The NRS and the DASH score improved (from 8.5 pre-operatively to 1.53 and from 87.5 to 24.6 respectively-p